Fridays for Future's Disruptive Potential: An Inconvenient Youth Between Moderate and Radical Ideas - Marquardt, Jens (Frontiers in Communication, 2020)
In December 2015, political leaders celebrated the Paris Agreement as a milestone in the global fight against climate change. Three years later, Greta Thunberg’s school strike outside the Swedish parliament inspired thousands of students around the world to protest against their political leaders’ inability to adequately respond to climate change. Envisioning livable climate futures for generations to come, the emerging ‘Fridays for Future’ (FFF) movement urges governments to take more radical action on climate change. While FFF has sparked discussions about climate change around the world, the movement’s effects on broader societal change remain unclear. We, therefore, explore how FFF has triggered debates beyond the necessity to tackle climate change and offer a framework to reflect upon the broader socio-political implications of the school strikes. We illustrate the contestation between different ideas of social life and political order encapsulated within and attached to FFF by analyzing the movement’s self-understanding and the media discourse around these protests in Germany. Although the German government portrays the country as a pioneer in moving an industry-based economy towards decarbonization, the school strikes have quickly emerged and stabilized. We explore if and how the FFF protestors express not only the need for climate action but also call for deeper societal transformation. To do so, our study draws upon a discourse analysis based on news articles, official documents, and speeches, complemented by qualitative interviews with youth representatives and experts involved in the movement to identify competing imaginaries and themes of contestation. We study the tensions between competing student-led visions of the future through the lens of sociotechnical imaginaries, which allows us to illuminate and juxtapose moderate and radical approaches. In conclusion, current school protests are not only about climate action but reflect more fundamental political struggles about competing visions of a future society in times of climate change. Yet, the protestors’ strong focus on science-driven politics risks to overshadow these broader societal debates, potentially stabilizing the techno-centric, apolitical and market-driven rationale behind climate action.